Muscle antioxidant (vitamin E) and major fatty acid groups, lipid oxidation and retail colour of meat from lambs fed a roughage based diet with flaxseed or algae. (January 2016) - Ponnampalam, Eric N.; Burnett, Viv F.; Norng, Sorn; Hopkins, David L.; Plozza, Tim; Jacobs, Joe L.
Abstract: The effect of feeding flaxseed or algae supplements to lambs on muscle antioxidant potential (vitamin E), major fatty acid groups, lipid oxidation and retail colour was investigated. Lambs (n = 120) were randomly allocated to one of 4 dietary treatments according to liveweight and fed the following diets for eight weeks: Annual ryegrass hay [60%] + subterranean clover hay [40%] pellets = Basal diet; Basal diet with flaxseed (10.7%) = Flax; Basal diet with algae (1.8%) = Algae; Basal diet with flaxseed (10.7%) and algae (1.8%) = FlaxAlgae. Flaxseed or algae supplementation significantly affected major fatty acid groups in muscle. The addition of algae (average of Algae and FlaxAlgae) resulted in lower vitamin E concentration in muscle ( P < 0.003; 1.0 vs 1.3 mg/kg of muscle) compared with lambs fed a diet without algae (average of Basal and Flax). Increasing muscle EPA + DHA by algae supplementation significantly increased lipid oxidation, but retail display colour of fresh meat was not affected.